Social protection schemes for workers in the informal sector: The case of health insurance in Tanzania - Rehema G. Kilonzo; Lutengano Mwinuka; Raphael Rasiel Macha (Roskilde University, Department of Social Sciences and Business, Socio-Economic Research Centre (SECO), 2023)
In order to achieve universal health coverage, the full involvement of informal-sector workers in healthinsurance schemes is necessary. In Tanzania, measures targeting informal-sector workers have been evolving over time. Earlier researchers reported low participation of such workers in the country's public health-insurance schemes, which mainly complemented workers in the formal sector, ignoring or not responding to the needs and challenges of informal workers. For reasons of sustainability, healthinsurance schemes need to incorporate a package of other benefits that address the actual needs of informal workers in both rural and urban areas. Implementation of the National Informal Sector Scheme (NISS) was thought to be of particular interest for informal-sector workers, as, by its design, it combined health insurance for such workers with access to small loans in order to cater for other life contingencies than health. In this paper, we use the case of health insurance under the NISS to answer the following questions: What strengths, weaknesses, opportunities and challenges are occasioned by the scheme? Was the scheme participatory and needs-based? Is it appropriate to integrate the health-insurance scheme with benefit packages like loans and credits as a pension scheme? What are the potential measures that could be used to boost the enrollment of informal workers in the NISS scheme? The study adopted a cross-sectional research design and gathered data and information from 35 key informants. Findings from the study indicate that performance of the health-insurance scheme under NISS mainly was influenced by: 1) the termination of medical service benefits for new NISS members after April 2019; 2) the limited number of accessible health facilities; 3) limited benefit packages, 4) inconvenient payment mechanisms for the members, and 5) a generally negative attitude on the part of informal-sector members and a lack of awareness of what NISS is all about. Like those working in formal-sector jobs, informal-sector workers in Tanzania also need access to good health services, soft loans and pension schemes. All key players, such as NHIF, NSSF, financial organizations and the apex organizations of informal-sector workers like the VIBINDO Society and SHIUMA Tanzania, have a great role to play in addressing the needs of informal-sector workers.
Keywords: 330; informal workers; social policy; informal-sector development; health insurance; policy